1960
DOI: 10.1113/jphysiol.1960.sp006570
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption in new‐born rats

Abstract: The rectal temperature of the newborn rat closely approximates to that of its environment. The ability of the rat to maintain a relatively constant body temperature in the cold is fairly well developed by the age of 3 weeks. Adolph (1957) concluded, largely from the work of Antoschkina (1939) and Fairfield (1948), that the newborn rat does not respond to cold with an increase in heat production (as indicated by an increase in 02 consumption) until the age of 3-4 days. If this were true, then the newborn rat wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
0
1

Year Published

1962
1962
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(102 citation statements)
references
References 25 publications
8
92
0
1
Order By: Relevance
“…Hill (1959) found that for kittens maintained at the neutral temperature, the oxygen concentration of inspired air could be reduced to 10% before oxygen consumption was affected. However, more relevant is the report of Taylor (1960) …”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Hill (1959) found that for kittens maintained at the neutral temperature, the oxygen concentration of inspired air could be reduced to 10% before oxygen consumption was affected. However, more relevant is the report of Taylor (1960) …”
Section: Apparatusmentioning
confidence: 99%
“…This, together with the small scatter and absence of seasonal change, provides grounds for confidence in the described technique, within its limitations, which might be included among tests to be used for the investigation of drugs administered at the time of childbirth. Fairfield (1948) 35-0 2-3 days 2-1-3-6 Gelineo & Gelineo (1951) 35.9 3-5 hr 1.90 Taylor (1960) 38-0 4 hr 1-97 Present study 38-0 4hr 180 The oxygen consumption of new-born from mothers treated with morphine, methadone or etorphine was reduced in proportion to the maternal dose level of narcotic, over a limited range, but no explanation can be offered for the apparently significant change in slope of the morphine response line at high doses (Fig. 2).…”
Section: >300mentioning
confidence: 99%
“…Er stiitzte seine Auffassung dabei im wesentlichen auf die Untersuchungen yon ANTOSCHKINA (1939( ) und FAIRFIELD (1948. In sp~iteren Untersuchungen wurde jedoch nachgewiesen, dat~ auch bei der neugeborenen Ratte in den ersten Lebenstagen eine Steigerung der Sauerstoffaufnahme dutch Abkiihlung eintritt (GELINEO ~i;GELINEO 1951, HA~tN & KOLDOVSKY 1958, TAYLOR 1960 (PIcHOTKA 1960, 1961, CHOINOWSKI 1962, HOHNSTADTER 1962 GELIN~O & GEI.mEO 1951, BAI~Id 1953, TAYLOR 1960.…”
Section: Und Beiunclassified
“…If Ta is very low, the pup may not be able to reach an area of higher temperature, resulting in further heat loss, with subsequent hypothermic immobility, additional heat loss, and, eventually, death. Although vascular response to lowered Ta has been suggested as early as 4 days of age (Poczopko, 1961), most researchers have found little evidence of this ability until 12-14 days of age in the rat (e.g., Conklin et al, 1971;Taylor, 1960). Furthermore, because most mice and rats are born without fur, they lack both passive (insulation provided by fur) and active (piloerection) means of reducing the rate of heat loss that are available to the adult.…”
mentioning
confidence: 99%